Mekanisme Penyelesaian Pembiayaan Bermasalah Pada Akad Murabahah (Studi Pada PT. BPRS Tanmiya Artha Kediri) - Sri Hariyanti; Dini Noviana; M. Yaskiyan Assyafik (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2023)
The development of the Islamic economy has recently begun to show a significant increase in Indonesia and the world. This is marked by the emergence of many Islamic banks, as well as Islamic rural banks. PT. BPRS Tanmiya Artha Kediri, which is one of the BPRS in the City of Kediri, has carried out Islamic financing as is done by other Islamic banks, but only serves murabahah financing. In the implementation of PT. BPRS Tanmiya Artha Kediri has experienced problems in the form of murabahah financing. This study aims to determine the factors that cause problematic murabahah financing and to determine the mechanism for resolving problematic murabahah financing contracts at PT. BPRS Tanmiya Artha Kediri. In this study, a qualitative descriptive method was used to analyze and describe the object under study. The results of this study conclude that the factors causing problematic financing in murabahah contracts are internal factors and external factors, then the mechanism for resolving problematic financing in murabahah contracts is by billing according to existing SOPs by providing SP 1,2 and 3, in a persuasive way (family), then By way of rescheduling (re-scheduling) which is to provide relief to customers by changing the customer's payment schedule, namely by extending the payment schedule or time period.